Chá Branco (Camelia simensis) diminui estresse oxidativo e triglicerídios em camundongos com obesidade induzida por dieta hiperlipídica - Lilian Goncalves Teixeira (2010)
Several studies suggest that green tea has beneficial effects on obesity and its related complications, mainly due to its antioxidant effects. White tea derivated of same plant (Camellia sinensis), has higher levels of catechins than green tea and has been popularly used for weight loss. However, there are no scientific studies supporting this effect. Our goal was to evaluate the effect of white tea intake on the obesity development and its complications in obese mice. For that, we developed a model of diet induced obesity associated to increased oxidative stress. After 8 weeks receiving such diet, C57BL/6 mice increased body weight, expansion of visceral fat associated to macrophages infiltration,increased oxidative stress and worse atherogenic lipoprotein profile when compared to mice fed chow diet. This model of diet induced obesity was used to evaluate the effects dietary supplementation of white tea extract in the obesity development during 8 experimental weeks. After that, mice receiving white tea free diet or diet plus 0.5% of white tea extract were sacrificed and blood, perigonadal fat and liver were collected. The percentage of visceral fat, adipocyte area, macrophage infiltration on perigonadal fat as well as serum lipid profile and glucose and oxidative stress parameters were studied. The results did not reinforce beneficial effects of white tea in reducing food intake or body weight. Moreover, there were no differences on the percentage of visceral fat and on the adipocyte area between groups. Similarly, no changes were seen in glucose homeostasis and lipoprotein profile in animals receiving white tea. Onthe other hand, a decrease in serum triglycerides associated to increased excretion of lipids was seen after white tea suplemmentation. Nonetheless, white tea intake reduced oxidative stress in liver and adipose tissue but not in the serum. We concluded that dietary white tea extract supplementation (0.5%) does not influence body weight or other parameters related to obesity. The possible beneficial effects of this tea are the reduction of oxidative stress and serum triglycerides in obese mice. Thus, the possible benefits of using tea can be restricted to the oxidative stress associate complications of obesity or hytriglyceridemia